Time and switching signal scheduled bumpless transfer control for switched systems with application to aero-engines. (May 2023) - Chen, Weizhong; Shi, Yan; Fei, Zhongyang
Abstract: In this paper, the time and switching signal scheduled bumpless transfer control (BTC) is addressed for switched systems with non-weighted L 2 -gain property. Considering that abrupt bumps of the controller at switching instants may lead to transient resonance effects or even failure of the system, a new BTC strategy is presented to alleviate control bumps. First, based on an introduced time scheduler, we propose the concept of the time and switching signal scheduled bumpless transfer (BT) performance. Then, by constructing a novel multiple discontinuous Lyapunov functional, relaxed criteria are established for the mixed L 2 -gain/switching signal scheduled BT performance of switched systems. Furthermore, tighter switching signals and time-dependent controllers are co-designed to accomplish both switching transient and L 2 -gain performance of the closed-loop system. Finally, an experiment on a hardware-in-the-loop of an aero-engine system is implemented to illustrate the validity and merits of the derived results.